Linking Zoopharmacognocy with Ethnomedication, An Evidence Base from Sebangau National Park, Central Kalimantan Indonesia - Adventus Panda; Yohanes Edy Gunawan (Journal of Tropical Life Science, 2018)
The ability of animal to perform self-medication has been studied decades, as well as their relationship with medication practices by communities. Long-term observation of Orangutans' behaviour (Pongo pygmaeus wurmbii), by communities surround Sebangau National Park, has suggested as their modes to today ethno-medication practice. The study was aimed to study the relationship of Orangutans self-medicate behavior with ethno-medication practice, in Sebangau area. The research was conducted in Punggualas, SNP, from 29 April to 03 October 2017. A number of 13 traditional healers (TH) from Karuing (n = 4), Baun Bango (n = 4), and Jahanjang (n = 5) have been interviewed. All plants are listed and photograph. Plants parts, and their mechanism of utilization were also kept for record. Meanwhile, the behavior followed the Orangutan protocol, with focus on their feeding behavior. All data were analyzed descriptively, while the relationship was analyzed using chi-square and F test. We have recorded a total 131 plants at various life forms, in Baun Bango (n = 59), Jahanjang (n = 41), and Karuing (n = 21). Plants that were found similar among three villages, removed, were only 95 left. We observed one female, showing the ability to perform self-mediaction. It is characterized by selectively choosing young leaves of Mezzetia sp., pulp of the Dyera lowii and Ilex cymosa, and lastly chew the entire leaves of Belang Handipek. It suggests a form of prevention against fatigue conditions, and the combination of these three plants species assume to be relating to fitness. This study shows that there is a relationship between the plant part used by the traditional healer and the orang- utan (x2 = 43,887; n = 115, df = 11, p-value = 0.0000), the relationship between the use of plant parts utilized by the traditional healer and orangutans (x2 = 15, 647; n = 50, df = 8, p-value = 0.0000). Furthermore, there is a relationship between the practice of traditional healer treatment using plant parts and Orang-utan (F1, 113 = 230.158; p-value = 0,000). The study urges to isolate secondary metabolites for further investigation, especially in terms of phyto-pharmacy.